Review of Literature on the Media Uses and Gratifications Derived By Students of Higher Education in India - Dr. Uma Bhushan, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2023)
This study is a brief review of the literature on the media uses and gratification among students of higher education in India. With the proliferation of social media and the pandemic-induced lockdown of the past two years, it is important to understand – how students use social media, seek and gain gratification from it, because with the proliferation of large number of social media networking sites and the magnitude of traffic that it generates, brands today put a significant weightage on promotions via these channels as the engagement metrics of these particular sites are new currencies of today’s connected world. The demography, ‘College going students’ was specifically chosen as they are consumers of tomorrow and their buying behaviour pattern will direct and shape the dimensions of future markets. The area of focus for this study was to review the published literature on the uses and gratifications of Media (specifically social media) uses among college going students through the lens of the ‘Uses and gratification’ theory. What are the gratifications sought and gratifications obtained through Social Networking Sites (hereinafter SNS)? Why people choose specific site/ service for a particular desire to be fulfilled? Why the internet – a great platform for searching and sharing information, is being utilized by college students primarily for communication and social networking activities rather than for the academic purposes? How the gratifications sought differ between males and females? What are the major motivations and needs for the consumers, belonging to demography stated above, to join SNS? The difference in treatment and the gratification sought from professional SNS like ‘LinkedIn’ and if there are any improvements or increase in efficiency in learning process due to incorporation of SNS in academics? The review found that Students prefer to spend more time online communicating and socialising using internet resources than devoting it for academic pursuits. Why people are so enamoured with social media is explained by its “user-friendly” and “let users manage” features as well as its user-generated material. Higher education students want to be involved in their communities; therefore, they seek out to their peer network in an effort to do so. Social fulfilment leads to adoption. College students use and built social capital on different social media platforms for gratification of their various desires. The gratifications sought and obtained varies from platform to platform.